CULINARY AND EDUCATIONAL TOURISM DESIGN IN MAIMOON PALACE WITH AN APPROACH TO HERITAGE URBAN LANDSCAPE - Zahara Prahastiwi; Bhakti Alamsyah; Ramadhani Fitri (Sean Institute, 2022)
North Sumatra consists of several tribes, namely, Malays tribe, Mandailing tribe, Toba tribe, Karo tribe, Simalungun tribe, Pakpak tribe, and Nias tribe. Each tribe has a variety of interesting cultures, especially the typical culinary that can give the identity of an area. Although the tribe in North Sumatra has a variety of typical culinary, in the city of Medan there is no special place that can be used as a place to find and learn the culinary specialties of North Sumatra. For that, needed a place to learn the culinary specialties of North Sumatra and also provide a place to eat the typical cuisine of North Sumatra without having to go to the tribal area of North Sumatra. North Sumatra’s educative culinary center is a means of learning the culinary specialties of North Sumatra that can make the people of Medan aware of the importance of maintaining traditional culinary North Sumatra. This Culinary Center is not only a place of education, this Culinary Center provides restaurants and food courts for the general public and tourists who want to try the culinary specialties of North Sumatra. This culinary center is located in the Maimoon Palace area. Maimoon's palace is one of the icons of the city of Medan, currently undergoing additional facilities, one of which is a culinary center facility. Because this Culinary Center is in the Palace area, This Culinary Center can support increase the existence of Maimoon Palace. This Culinary Center applies Contextual Themes and Concepts that are in context with Maimoon Palace and Kasawan Maimoon Palace..